2018
DOI: 10.2147/dddt.s160300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nocturnal symptoms in advanced Parkinson’s disease patients with sleep disturbances: pramipexole sustained release versus immediate release formulations

Abstract: BackgroundNocturnal symptoms are common in Parkinson’s disease (PD), which greatly affect the quality of life but are often overlooked in clinical settings. Treatment strategies that provide sustained dopaminergic stimulation may have sleep benefits.ObjectiveTo investigate the treatment effects of pramipexole (PPX) sustained release (SR) versus PPX immediate release (IR) on nocturnal symptoms in advanced PD patients with sleep disturbances.Materials and methodsIn this study, the PPX clinical trial (NCT00466167… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“… 4 , 5 Pramipexole, a dopamine receptor agonist, was approved for the treatment of early and late PD in the United States and Europe in 1998. 6 Through a neuroprotective effect, pramipexole delays levodopa-induced motor complications in early PD, controls motor symptoms, and relieves depression in PD patients. 7 A recent study demonstrated that inflammatory cytokines are abnormally expressed in patients with neurodegenerative diseases and are involved in disease development.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Pramipexole, a dopamine receptor agonist, was approved for the treatment of early and late PD in the United States and Europe in 1998. 6 Through a neuroprotective effect, pramipexole delays levodopa-induced motor complications in early PD, controls motor symptoms, and relieves depression in PD patients. 7 A recent study demonstrated that inflammatory cytokines are abnormally expressed in patients with neurodegenerative diseases and are involved in disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the replacement of lost dopamine with dopaminergic drugs in 24 h is necessary for the management of motor symptoms alone – regardless of whether these occur nocturnally or during the daytime. Adjunctive medications [ 31 33 ], infusion systems such as DuoDopa (carbidopa/levodopa) [ 34 ], continuous dopamine delivery treatments like the transdermal rotigotine patch [ 35 39 ], and oral extended release versions of dopamine agents [ 40 , 41 ] have shown significant promise in ameliorating wearing-off effects and symptom fluctuations, in nocturnal as well as daytime symptoms. In a randomized, placebo-controlled study (the RECOVER trial, quality score, 93%), patients with unsatisfactory control of early morning motor symptoms were evaluated on the PDSS-2 and UPDRS III.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern of improvement of insomnia symptoms among individuals with advanced PD and insomnia symptoms (PDSS <90) was observed with the addition of pramipexole sustained release or immediate release (IR). 50 Although individuals experienced significant increases in the PDSS total, global sleep quality, and nocturnal motor symptoms subscales over time with either pramipexole formulation, individuals receiving the sustained release experienced larger (but nonsignificant) improvements over the IR.…”
Section: Treatments Of Insomnia In Pd Dopaminergic Medications For Inmentioning
confidence: 94%